2018
DOI: 10.1111/clr.13371
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human BMP9 (RhBMP9) in comparison with rhBMP2 for ridge augmentation following tooth extraction: An experimental study in the Beagle dog

Abstract: Objectives The purpose of this study was to compare the effects of rhBMP2 with rhBMP9 on ridge augmentation following healing of extraction sockets in dogs. Material and methods Five male Beagle dogs, approximately 12 months of age, were used. The mesial roots of the four maxillary premolars were endodontically treated. The distal roots were extracted, and the buccal bony walls removed. All extraction sockets were filled with deproteinized bovine bone mineral (DBBM). A collagen membrane was soaked with 4 μg or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Three of them for sockets preservation as test group used BMP-2 [45-47] and collagen sponge [46], demineralized bone [45] or hydroxyapatite [47] as matrix. One study used MSC [48] and collagen membrane as a matrix, another one used BMP-9 [49] and collagen membrane, and in one study sockets were filled with bone marrow without any matrix [50]. The difference of socket width between test and control groups varies from 0.64 to 1.279 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of them for sockets preservation as test group used BMP-2 [45-47] and collagen sponge [46], demineralized bone [45] or hydroxyapatite [47] as matrix. One study used MSC [48] and collagen membrane as a matrix, another one used BMP-9 [49] and collagen membrane, and in one study sockets were filled with bone marrow without any matrix [50]. The difference of socket width between test and control groups varies from 0.64 to 1.279 mm.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main issues identified in previous and current reports is the dosage of the recombinant protein and the delivery method. Either absorbable collagen sponges [46,52] or mineralized grafts [45,47,49] have been identified as carriers in the current review. In both cases, the addition of the protein seems to induce better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kobayashi [55] evidenced that even the lower doses of BMP9 had higher levels of osteogenic differentiation than BMP2. Saulacic [56] used different carriers soaked in rhBMP2 or rhBMP9 to implant into the extraction fossa of dogs to compare the healing effect. The results showed that the rhBMP9 group had a more remarkable bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that BMP9 may play an important role in tooth and dentoalveolar development. BMP9 can regulate dentin formation, root development, and alveolar crest height ( Saulacic et al, 2018 ; Li et al, 2021a ). BMP9 knockout (KO) mice show significant defects in the dentoalveolar bone complex ( Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%